High-performance conductive silver paste for metal copper foil and preparation method of high-performance conductive silver paste
By using components such as silver powder corrosion inhibitors in conductive silver paste, the problem of poor acid and alkali resistance of existing conductive silver paste is solved, and higher comprehensive performance and cost-effectiveness are achieved.
Patent Information
- Application Number
- CN202411977962.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-25
AI Technical Summary
The existing conductive silver paste has poor acid and alkali resistance and large quality fluctuations, which affects the life of power tool switches.
High-performance conductive silver paste is prepared through specific preparation and mixing processes using components such as silver powder corrosion inhibitor, conductive graphite, ultrafine glass powder, polymer resin and organic solvent.
It significantly improves the acid and alkali resistance of conductive silver powder and improves the comprehensive performance of conductive silver paste. The product has higher cost-effectiveness, and has significantly improved acid resistance, alkali resistance and oxidation resistance.
Smart Images

Figure BDA0005220872100000031 
Figure BDA0005220872100000041 
Figure BDA0005220872100000051
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of conductive silver paste, and in particular to a high-performance conductive silver paste for metal copper foil and a preparation method thereof. Background Art
[0002] With the continuous development of science and technology, the integration of microelectronic circuits is getting higher and higher, the functions of smart devices are becoming more and more powerful, and the comprehensive performance requirements of copper clad laminates are also getting higher and higher. The heat dissipation and wear resistance of copper clad laminates are the core difficulties that need to be solved. At the same time, given that microelectronic circuits are likely to be exposed to hot and humid environments, as well as the influence of the atmosphere during sea transportation, improving the acid and alkali resistance of copper clad laminates has also become one of the core difficulties to be solved.
[0003] At present, most of the silver paste used in domestic electronic factories is domestically produced, and a small number of them use foreign products such as Japan's Fujikura. The main problems are as follows: the acid and alkali resistance of the silver paste is poor, the quality fluctuates greatly, and the life of the power tool switch is affected. Summary of the invention
[0004] The purpose of the present invention is to overcome the defects of the above-mentioned prior art and provide a high-performance conductive silver paste for metal copper foil and a preparation method thereof.
[0005] The purpose of the present invention can be achieved by the following technical solutions:
[0006] One of the technical solutions of the present invention is to provide a high-performance conductive silver paste for metal copper foil, wherein the raw materials are the following components and weight percentage contents:
[0007] Conductive silver powder 40-60%; conductive graphite 3-6%; silver powder corrosion inhibitor 0-2%; molybdenum disulfide 0-2%; ultrafine glass powder 0-2%; polymer resin 15-30%; organic solvent 10-30%; plasticizer 0-3%.
[0008] In some specific embodiments, the conductive silver powder is a flaky silver powder with an average particle size of 2.0-5.0 μm, a bulk density of 0.8-1.4 g / mL, a tap density of 1.8-3.0 g / mL, and a specific surface area of 0.7-1.4 m 2 / g.
[0009] In some specific embodiments, the conductive graphite is anisometric flake graphite with a particle size of 6.5 nm and a density of 0.07 g / cm 3 , with a specific surface area of 17m 2 / g.
[0010] In some specific embodiments, the silver powder corrosion inhibitor is selected from any one of 1-phenyl-5-mercaptotetrazolyl (PMTA), 2-mercaptobenzoxazole (MBO), 2-mercaptobenzimidazole (MBI), and 2-mercaptobenzothiazole (MBT).
[0011] In some specific embodiments, the average particle size of the molybdenum disulfide is 2.0-3.0 μm.
[0012] In some specific embodiments, the ultrafine glass powder has an average particle size of 0.5-2.0 μm, a sintering temperature of 550-650°C, a softening point of about 450°C, and comprises the following components and their weight percentages: Bi2O355-75, B2O3 10-30, ZnO 2-5, SiO2 2-5, CaF2 2-5, Al2O3 1-3, MgO 0.2-1, and Sb2O3 0.2-1.
[0013] In some specific embodiments, the polymer resin is selected from a mixture of any one or more of chloroacetic resin, polyurethane, phenolic resin, acrylic resin, and epoxy resin.
[0014] In some specific embodiments, the organic solvent is selected from any one or more of terpineol, diethylene glycol ethyl ether, diethylene glycol butyl ether, butyl carbitol acetate, dipropylene glycol monomethyl ether, and propylene glycol methyl ether propionate.
[0015] In some specific embodiments, the plasticizer is selected from any one or more of dibutyl phthalate, tributyl citrate, dioctyl phthalate, and trioctyl citrate.
[0016] The second technical solution of the present invention is to provide a method for preparing a high-performance conductive silver paste for metal copper foil as described in one of the above technical solutions, comprising the following steps:
[0017] (1) Prepare the materials according to the following components and weight percentages:
[0018] Conductive silver powder 40-60%; conductive graphite 3-6%; silver powder corrosion inhibitor 0-2%; molybdenum disulfide 0-2%; ultrafine glass powder 0-2%; polymer resin 15-30%; organic solvent 10-30%; plasticizer 0-3%.
[0019] (2) Preparation of organic carrier: Weigh the polymer resin and the organic solvent, and then heat them to 70°C and keep the temperature constant. After the polymer resin is completely dissolved, filter on a 300-400 mesh cloth to remove impurities, and thus obtain the organic carrier;
[0020] (3) Preparation of conductive silver paste: Conductive silver powder, conductive graphite, molybdenum disulfide, ultrafine glass powder, plasticizer, and silver powder corrosion inhibitor are weighed, and then fully mixed with an organic carrier in a mixer, and then dispersed at high speed using a high-speed dispersant to obtain a uniform slurry;
[0021] (4) Production of conductive silver paste: The above-mentioned paste is ground in a three-roll mill, and the fineness of the silver paste is controlled to be below 15 μm and the viscosity is 10-20 Pa·S by roller fine-tuning, thereby preparing a high-performance conductive silver paste for metal copper foil.
[0022] Compared with the prior art, the present invention significantly improves the acid and alkali resistance of conductive silver powder and comprehensively improves the comprehensive performance of conductive silver paste through the selection of silver powder corrosion inhibitor, and the product has a higher cost performance. The principle is: the silver powder corrosion inhibitor will form a protective film on the surface of the silver powder, isolating the silver powder from the environmental medium, and can effectively absorb ultraviolet rays to prevent the silver powder from reacting with various substances in the environment, thereby achieving a protective effect. On the other hand, through the selection and matching of polymer resins, multi-functional epoxy resins are used to improve the bonding performance between the conductive silver paste and the metal copper foil, and phenolic resins are used to take into account the silk screen printing process characteristics of the conductive silver paste. DETAILED DESCRIPTION
[0023] The present invention is described in detail below in conjunction with specific embodiments. This embodiment is implemented based on the technical solution of the present invention, and provides a detailed implementation method and a specific operation process, but the protection scope of the present invention is not limited to the following embodiments.
[0024] In the following examples and comparative examples, the polymer resin is selected from epoxy resin and phenolic resin, wherein the epoxy resin is one of TDE-85, AG-80 and AFG-90, and the phenolic resin is PR50235. The rest of the raw materials or processing techniques, unless otherwise specified, are conventional commercially available raw materials or conventional processing techniques in the art.
[0025] Example 1
[0026] (1) Prepare 100g of material according to the following composition and mass:
[0027]
[0028] The particle size of the silver flake powder used is 2.89 μm, the bulk density is 1.22 g / mL, the tap density is 2.44 g / mL, and the specific surface area is 0.84 m 2 / g;
[0029] The conductive graphite used is highly anisometric flake graphite with an original particle size of 6.50nm and a density of 0.07g / cm 3 , with a specific surface area of 17m 2 / g;
[0030] The molybdenum disulfide used was of natural grade with an average particle size of 2.43 μm;
[0031] The composition and weight percentage of the ultrafine glass powder used are: Bi2O3 66, B2O3 22, ZnO 3, SiO2 4, CaF22, Al2O3 1.5, MgO 1, Sb2O3 0.3, the average particle size is 1.45μm, and the softening point is 450℃;
[0032] (2) Preparation of organic carrier: weigh phenolic resin PR50235 and diethylene glycol ethyl ether, then heat them to 70° C. and keep the temperature constant. After the phenolic resin is completely dissolved, filter on a 300-400 mesh cloth to remove impurities, thereby obtaining an organic carrier;
[0033] (3) Preparation of conductive silver paste: After weighing flaky silver powder, conductive graphite, silver powder corrosion inhibitor PMTA, molybdenum disulfide, ultrafine glass powder, and plasticizer DBP, they are fully mixed with an organic carrier and epoxy resin TDE-85 in a mixer, and then dispersed at high speed using a high-speed dispersant to obtain a uniform slurry;
[0034] (4) Production of conductive silver paste: The above-mentioned paste is ground five times in a three-roll mill, and the fineness of the silver paste is controlled to be 10 μm and the viscosity to be 15 Pa·S by fine adjustment of the rollers, thereby obtaining a high-performance conductive silver paste for metal copper foil.
[0035] Example 2
[0036] (1) Prepare 100g of material according to the following composition and mass:
[0037]
[0038] The particle size of the silver flake powder used is 2.89 μm, the bulk density is 1.22 g / mL, the tap density is 2.44 g / mL, and the specific surface area is 0.84 m 2 / g;
[0039] The conductive graphite used is highly anisometric flake graphite with an original particle size of 6.50nm and a density of 0.07g / cm 3 , with a specific surface area of 17m 2 / g;
[0040] The molybdenum disulfide used was of natural grade with an average particle size of 2.43 μm;
[0041] The composition and weight percentage of the ultrafine glass powder used are: Bi2O3 66, B2O3 22, ZnO 3, SiO2 4, CaF22, Al2O3 1.5, MgO 1, Sb2O3 0.3, the average particle size is 1.45μm, and the softening point is 450℃;
[0042] (2) Preparation of organic carrier: Phenolic resin PR50235 and diethylene glycol butyl ether were weighed, and then heated to 70° C. and kept at a constant temperature. After the phenolic resin was completely dissolved, it was filtered on a 300-400 mesh cloth to remove impurities, thereby obtaining an organic carrier;
[0043] (3) Preparation of conductive silver paste: weigh flaky silver powder, conductive graphite, silver powder corrosion inhibitor MBO, molybdenum disulfide, ultrafine glass powder, and plasticizer, and fully mix them with organic carrier and epoxy resin AFG-90 in a mixer, and then use a high-speed dispersant for high-speed dispersion to obtain a uniform slurry;
[0044] (4) Production of conductive silver paste: The above-mentioned paste is ground five times in a three-roll mill, and the fineness of the silver paste is controlled to 11 μm and the viscosity to 13 Pa·S by fine adjustment of the rollers, thereby obtaining a high-performance conductive silver paste for metal copper foil.
[0045] Example 3
[0046] (1) Prepare 100g of material according to the following composition and mass:
[0047]
[0048] The particle size of the silver flake powder used is 2.89 μm, the bulk density is 1.22 g / mL, the tap density is 2.44 g / mL, and the specific surface area is 0.84 m 2 / g;
[0049] The conductive graphite used is highly anisometric flake graphite with an original particle size of 6.50nm and a density of 0.07g / cm 3 , with a specific surface area of 17m 2 / g;
[0050] The molybdenum disulfide used was of natural grade with an average particle size of 2.43 μm;
[0051] The composition and percentage of the ultrafine glass powder used are: Bi2O3 66, B2O3 22, ZnO 3, SiO2 4, CaF2 2, Al2O3 1.5, MgO 1, Sb2O3 0.3, the average particle size is 1.45μm, and the softening point is 450℃;
[0052] (2) Preparation of organic carrier: Phenolic resin PR50235 and diethylene glycol butyl ether were weighed, and then heated to 70° C. and kept at a constant temperature. After the phenolic resin was completely dissolved, it was filtered on a 300-400 mesh cloth to remove impurities, thereby obtaining an organic carrier;
[0053] (3) Preparation of conductive silver paste: Weigh flaky silver powder, conductive graphite, silver powder corrosion inhibitor MBI, molybdenum disulfide, ultrafine glass powder, and plasticizer, fully mix with organic carrier and epoxy resin TDE-85 in a mixer, and then use a high-speed dispersant for high-speed dispersion to obtain a uniform slurry;
[0054] (4) Production of conductive silver paste: The above-mentioned paste is ground five times in a three-roll mill, and the fineness of the silver paste is controlled to 11 μm and the viscosity to 12 Pa·S by fine adjustment of the rollers, thereby obtaining a high-performance conductive silver paste for metal copper foil.
[0055] Example 4
[0056] (1) Prepare 100g of material according to the following composition and mass:
[0057]
[0058] The particle size of the silver flake powder used is 2.89 μm, the bulk density is 1.22 g / mL, the tap density is 2.44 g / mL, and the specific surface area is 0.84 m 2 / g;
[0059] The conductive graphite used is highly anisometric flake graphite with an original particle size of 6.50nm and a density of 0.07g / cm 3 , with a specific surface area of 17m 2 / g;
[0060] The molybdenum disulfide used was of natural grade with an average particle size of 2.43 μm;
[0061] The composition and percentage of the ultrafine glass powder used are: Bi2O3 66, B2O3 22, ZnO 3, SiO2 4, CaF2 2, Al2O3 1.5, MgO 1, Sb2O3 0.3, the average particle size is 1.45μm, and the softening point is 450℃;
[0062] (2) Preparation of organic carrier: Phenolic resin PR50235 and diethylene glycol butyl ether were weighed, and then heated to 70° C. and kept at a constant temperature. After the phenolic resin was completely dissolved, it was filtered on a 300-400 mesh cloth to remove impurities, thereby obtaining an organic carrier;
[0063] (3) Preparation of conductive silver paste: weigh flaky silver powder, conductive graphite, silver powder corrosion inhibitor MBT, molybdenum disulfide, ultrafine glass powder, and plasticizer, fully mix with organic carrier and epoxy resin AG-80 in a mixer, and then use a high-speed dispersant for high-speed dispersion to obtain a uniform slurry;
[0064] (4) Production of conductive silver paste: The above-mentioned paste is ground five times in a three-roll mill, and the fineness of the silver paste is controlled to 8 μm and the viscosity to 13 Pa·S by fine adjustment of the rollers, thereby obtaining a high-performance conductive silver paste for metal copper foil.
[0065] Comparative Example 1
[0066] (1) Prepare 100g of material according to the following composition and mass:
[0067]
[0068] The particle size of the silver flake powder used is 2.89 μm, the bulk density is 1.22 g / mL, the tap density is 2.44 g / mL, and the specific surface area is 0.84 m 2 / g;
[0069] The conductive graphite used is highly anisometric flake graphite with an original particle size of 6.50nm and a density of 0.07g / cm 3 ;
[0070] The molybdenum disulfide used was of natural grade with an average particle size of 2.43 μm;
[0071] The composition and percentage of the ultrafine glass powder used are: Bi2O3 66, B2O3 22, ZnO 3, SiO2 4, CaF2 2, Al2O3 1.5, MgO 1, Sb2O3 0.3, the average particle size is 1.45μm, and the softening point is 450℃;
[0072] (2) Preparation of organic carrier: weigh phenolic resin PR50235 and diethylene glycol ethyl ether, then heat them to 70° C. and keep the temperature constant. After the phenolic resin is completely dissolved, filter on a 300-400 mesh cloth to remove impurities, thereby obtaining an organic carrier;
[0073] (3) Preparation of conductive silver paste: Weigh flaky silver powder, conductive graphite, molybdenum disulfide, ultrafine glass powder, and plasticizer, mix them thoroughly with organic carrier and epoxy resin TDE-85 in a mixer, and then use a high-speed dispersant to disperse them at high speed to obtain a uniform slurry;
[0074] (4) Production of conductive silver paste: The above-mentioned paste is ground five times in a three-roll mill, and the fineness of the silver paste is controlled to be 10 μm and the viscosity to be 15 Pa·S by fine adjustment of the rollers, thereby obtaining a high-performance conductive silver paste for metal copper foil.
[0075] The difference between Examples 1, 2, 3, 4 and Comparative Example 1 is that in Examples 1, 2, 3, 4, different silver powder corrosion inhibitors are added on the basis of Comparative Example 1, respectively, the polymer resin part is the same, and the flaky silver powder is the same system. The following screen printing process is used to screen print on the PCB board to conduct national standard acid and alkali resistance test evaluation, and the test results are as follows:
[0076] serial number Example 1 Example 2 Example 3 Example 4 Comparative Example 1 Silver content 50% 60% 50% 60% 50% hardness 5H 5H 5H 5H 5H Acid resistance Resistance Resistance Resistance Resistance Intolerance Alkali resistance Resistance Resistance Resistance Resistance Intolerance Antioxidant excellent excellent excellent excellent generally
[0077] It can be seen from the above test results that the silver paste prepared by this method is very excellent in acid resistance, alkali resistance and oxidation resistance, especially in acid resistance and alkali resistance, which has been greatly improved.
[0078] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.
Claims
1. A high-performance conductive silver paste for metal copper foil, characterized in that: The raw materials use the following components and weight percentages: Conductive silver powder 40-60%; conductive graphite 3-6%; silver powder corrosion inhibitor 0-2%; molybdenum disulfide 0-2%; ultrafine glass powder 0-2%; polymer resin 15-30%; organic solvent 10-30%; plasticizer 0-3%.
2. The high-performance conductive silver paste for metal copper foil according to claim 1, characterized in that: The conductive silver powder is a flaky silver powder with an average particle size of 2.0-5.0 μm, a loose density of 0.8-1.4 g / mL, a tap density of 1.8-3.0 g / mL, and a specific surface area of 0.7-1.4 m 2 / g.
3. The high-performance conductive silver paste for metal copper foil according to claim 1, characterized in that: The conductive graphite is anisometric flake graphite with a particle size of 6.5 nm and a density of 0.07 g / cm 3 , with a specific surface area of 17m 2 / g.
4. The high-performance conductive silver paste for metal copper foil according to claim 1, characterized in that: The silver powder corrosion inhibitor is selected from any one of 1-phenyl-5-mercaptotetrazolyl (PMTA), 2-mercaptobenzoxazole (MBO), 2-mercaptobenzimidazole (MBI), and 2-mercaptobenzothiazole (MBT).
5. The high-performance conductive silver paste for metal copper foil according to claim 1, characterized in that: The average particle size of the molybdenum disulfide is 2.0-3.0 μm.
6. The high-performance conductive silver paste for metal copper foil according to claim 1, characterized in that: The ultrafine glass powder has an average particle size of 0.5-2.0 μm and comprises the following components and weight percentages: Bi2O3 55-75, B2O3 10-30, ZnO 2-5, SiO2 2-5, CaF2 2-5, Al2O3 1-3, MgO 0.2-1, and Sb2O30.2-1.
7. The high-performance conductive silver paste for metal copper foil according to claim 1, characterized in that: The polymer resin is selected from a mixture of any one or more resins selected from chloroacetic resin, polyurethane, phenolic resin, acrylic resin, and epoxy resin.
8. The high-performance conductive silver paste for metal copper foil according to claim 1, characterized in that: The organic solvent is selected from any one or more of terpineol, diethylene glycol ethyl ether, diethylene glycol butyl ether, butyl carbitol acetate, dipropylene glycol monomethyl ether, and propylene glycol methyl ether propionate.
9. The high-performance conductive silver paste for metal copper foil according to claim 1, characterized in that: The plasticizer is selected from any one or more of dibutyl phthalate, tributyl citrate, dioctyl phthalate and trioctyl citrate.
10. A method for preparing a high-performance conductive silver paste for metal copper foil according to any one of claims 1 to 9, characterized in that: The steps include: (1) Prepare the materials according to the following components and weight percentages: Conductive silver powder 40-60%; conductive graphite 3-6%; silver powder corrosion inhibitor 0-2%; molybdenum disulfide 0-2%; ultrafine glass powder 0-2%; polymer resin 15-30%; organic solvent 10-30%; plasticizer 0-3%. (2) Preparation of organic carrier: Weigh the polymer resin and the organic solvent, and then heat them to 70°C and keep the temperature constant. After the polymer resin is completely dissolved, filter on a 300-400 mesh cloth to remove impurities, and thus obtain the organic carrier; (3) Preparation of conductive silver paste: Conductive silver powder, conductive graphite, molybdenum disulfide, ultrafine glass powder, plasticizer, and silver powder corrosion inhibitor are weighed, and then fully mixed with an organic carrier in a mixer, and then dispersed at high speed using a high-speed dispersant to obtain a uniform slurry; (4) Production of conductive silver paste: The above-mentioned paste is ground in a three-roll mill, and the fineness of the silver paste is controlled to be below 15 μm and the viscosity is 10-20 Pa·S by roller fine-tuning, thereby preparing a high-performance conductive silver paste for metal copper foil.